Disruption of Plasmodium falciparum Chitinase Markedly Impairs Parasite Invasion of Mosquito Midgut - Tsai, Yao-Lung (American Society for Microbiology, 2001)
To initiate invasion of the mosquito midgut, Plasmodium ookinetes secrete chitinolytic activity to penetrate the peritrophic matrix surrounding the blood meal. While ookinetes of the avian malaria parasite Plasmodium gallinaceum appear to secrete products of two chitinase genes, to date only one chitinase gene, PfCHT1, has been identified in the nearly completed Plasmodium falciparum strain 3D7 genome database. To test the hypothesis that the single identified chitinase of P. falciparum is necessary for ookinete invasion, the PfCHT1 gene was disrupted 39 bp upstream of the stop codon. PfCHT1-disrupted parasites had normal gametocytogenesis, exflagellation, and ookinete formation but were markedly impaired in their ability to form oocysts in Anopheles freeborni midguts. Confocal microscopy demonstrated that the truncated PfCHT1 protein was present in mutant ookinetes but that the concentration of mutant PfCHT1 within the apical end of the ookinetes was substantially reduced. These data suggest that full-length PfCHT1 is essential for intracellular trafficking and secretion and that the PfCHT1 gene product is necessary for ookinetes to invade the mosquito midgut.